“They said I came back Americanized”: cosmopolitanism and mediation in the trajectory of Carmen Miranda - Julia O’Donnell (Ateliers d'Anthropologie)
This paper analyzes Carmen Miranda’s trajectory by situating it in the broader context of the disputes about Brazilian nationality between 1920 and 1940. At the intersection between her career and the Brazilian political culture of her time, the paper discusses her role in mediating the symbols that contributed to a particular national project that made the samba the country’s unmistakable trademark.